Literature Review: Impact and Implications of Involvement Ulama's Involvement in the Business World - Hakim, Abdul; Sani, Abdul; Arabi, Ibnu; El-Azkia Rumisa, Shupia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research explores the impact and implications of ulama involvement in the business world, which is increasingly important in the context of Islamic economics. Ulama, traditionally known as spiritual leaders, are now also playing a significant role in business, especially in ensuring shariah-compliant business practices. This study analyzes the influence of ulama involvement on business practices, economic impact, social impact, and the challenges and moral implications faced. The results show that the involvement of ulama in business encourages the integration of sharia values, such as fairness and transparency, in business operations. It also increases consumer trust and loyalty, which contributes to the economic growth of sharia-based businesses. In addition, ulama play an important role in promoting corporate social responsibility (CSR) and social justice. However, a key challenge faced is the potential conflict of interest between the religious and commercial roles of ulama, as well as the risk of erosion of moral authority if involvement in business is not properly managed. This research recommends specialized education and training for ulama, the establishment of Islamic business ethics committees, and increased collaboration between ulama and business professionals. By doing so, ulama can continue to serve as agents of change who promote ethical and equitable business practices, while maintaining their moral integrity. The results of this study provide valuable insights for stakeholders in managing the role of ulama in the business world in the future.